2019
DOI: 10.46622/jogea.v2i1.2483
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of Integrating Indigenous Knowledge in the teaching of weather and climate in Geography in Manicaland province of Zimbabwe

Abstract: Scholars have acknowledged that the current education system in Zimbabwe has done very little to incorporate learners’ socio-cultural experiences. The purpose of the qualitative case study, from which this research draws its data, was to examine the views of the teachers and education officers on the challenges of integrating Indigenous Knowledge (IK) into the teaching of weather and climate. The study was conducted in secondary schools of Manicaland in Zimbabwe. It is hoped that these views from the various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Interestingly, this knowledge had been transmitted to the younger generation through riddles, songs, legends and myths. These results are consistent with previous studies (Bhatasara & Mandizadza, 2014;Chanza & Mafongoya, 2017;Mapara, 2009;Mapfumo et al, 2015;Mubaya et al, 2017;Risiro et al, 2012).…”
Section: Resultantly It Was Learnt Thatsupporting
confidence: 94%
“…Interestingly, this knowledge had been transmitted to the younger generation through riddles, songs, legends and myths. These results are consistent with previous studies (Bhatasara & Mandizadza, 2014;Chanza & Mafongoya, 2017;Mapara, 2009;Mapfumo et al, 2015;Mubaya et al, 2017;Risiro et al, 2012).…”
Section: Resultantly It Was Learnt Thatsupporting
confidence: 94%
“…These traditional ceremonies are done to request the ancestors to provide communities with rain and protection from pandemics. In a study carried out in the Eastern Highlands of Zimbabwe, Risiro (2020) found that traditional ceremonies were performed in sacred forests and mountains to request ancestors for good rains, good health and protection from environmental hazards.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The current critical discourse on the implementation of Ubuntu as an indigenous ideology for decolonising Zimbabwe's school curriculum produced contradictory indicators. While some Heritage Studies, Social Studies, Geography and Shona language teachers were making commendable efforts to implement Ubuntu in their practice (Dzvimbo, 2019;Risiro, 2019;Viriri, 2018), most studies indicated that a considerable number of teachers harbored negative attitudes towards Ubuntu and were not interested in practising it (Gasva et al, 2021;Madzanire, 2019;Makoni et al 2020;Rutsate & Rutsate, 2021). This was due to negative attitudes towards IKS, the influence of Christianity, urbanization, and teachers' lack of knowledge of Ubuntu.…”
Section: Discussionmentioning
confidence: 99%
“…In Lack of knowledge and training on Ubuntu, and a shortage of indigenous knowledge experts conversant with Ubuntu ethos remains a major impediment to the promotion of communitarian values of knowledge sharing and co-operation between teachers and elderly community members (Makoni et al, 2020;Risiro, 2019). Not all teachers understood Indigenous Knowledge Systems and Ubuntu.…”
Section: Theme 3: Corruption and The Undermining Of Ubuntu Valuesmentioning
confidence: 99%
See 1 more Smart Citation